Quantificação de biomarcadores em pacientes com fibromialgia submetidos a terapia com acupuntura - Steffen, Elizandra Leal (2021)
Fibromyalgia (FM) is a syndrome characterized by chronic, diffuse pain and systemic symptoms. Its etiology and pathogenesis are still not completely understood. The therapy used in FM mainly consists of the use of medications (analgesics, antiinflammatories, antidepressants and muscle relaxants), however, nonpharmacological therapies, such as acupuncture, have stood out in the treatment of this syndrome because it provides pain relief and greater physical well-being for patients. The present research aimed to quantify and evaluate the levels of laboratory biomarkers, highlighting some pro- and anti-inflammatory cytokines in patients with FM undergoing acupuncture. A total of 40 female patients between 20 and 60 years old, diagnosed with FM according to the criteria of the American College of Rheumatology, were randomized into two groups: Acupuncture - A (n = 20), which received real acupuncture and Sham - Y (n = 20), who received placebo acupuncture. The interventions took place once a week, for four consecutive weeks, lasting 30 minutes each. The patients underwent two blood samples: one before the first session of A or S and another after the fourth and last session of interventions. A third group (control - C), composed of 16 healthy women, was submitted to a single blood collection, without any intervention. The results obtained through the complete blood count, total cholesterol, triglycerides, uric acid, creatinine, C-reactive protein, creatinokinase, interleukin-2, interleukin-4, interleukin-6, interleukin-10, tumor necrosis factor-α (TNF- α ), interferon-gamma (IFN-ᵧ) and interleukin-17A were analyzed using IBM SPSS Version 25 software, assuming a significance of 5%. Significantly increased values in the distribution range of red blood cells, uric acid, C-reactive protein and triglycerides were detected in patients with FM (A and S) in relation to control, before acupuncture interventions. There was a significant difference in the platelet count of group A compared to group S, before the interventions, however, after 4 weeks of acupuncture, both groups did not show significant difference in the platelet count. Among the dosed cytokines, fibromyalgia patients had reduced serum levels of TNF-α and increased serum levels of IFN-ᵧ compared to control, before interventions. It was observed that patients with FM have some altered biochemical, hematological and immunological results in relation to the control. However, acupuncture did not change cytokine levels significantly.